2009
DOI: 10.1091/mbc.e07-11-1132
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Clustering of STIM1 with Orai1/CRACM1 at the Plasma Membrane Depends Dynamically on Depletion of Ca2+ Stores and on Electrostatic Interactions

Abstract: Activation of store operated Ca2؉ entry involves stromal interaction molecule 1 (STIM1), localized to the endoplasmic reticulum (ER), and calcium channel subunit (Orai1/CRACM1), localized to the plasma membrane. Confocal microscopy shows that thapsigargin-mediated depletion of ER Ca 2؉ stores in RBL mast cells causes a redistribution of STIM1, labeled with monomeric red fluorescent protein (mRFP), to micrometer-scale ER-plasma membrane junctions that contain Orai1/CRACM1, labeled with monomeric Aequorea coerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
144
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(154 citation statements)
references
References 41 publications
9
144
0
Order By: Relevance
“…We speculate that impaired translocation resulted from disrupted electrostatic interactions between the negative charges in this region and corresponding positive charges in the BmOrai1B C terminus. In support of this hypothesis, Calloway et al (45) reported that mutation of acidic residues in the cytoplasmic tail of Orai1 reduced STIM1 interactions, suggesting that electrostatic forces are involved in STIM1/Orai1 binding. In addition, we also showed that both the N and C termini of BmOrai1B are necessary for complete translocation of BmSTIM1 to the plasma membrane (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…We speculate that impaired translocation resulted from disrupted electrostatic interactions between the negative charges in this region and corresponding positive charges in the BmOrai1B C terminus. In support of this hypothesis, Calloway et al (45) reported that mutation of acidic residues in the cytoplasmic tail of Orai1 reduced STIM1 interactions, suggesting that electrostatic forces are involved in STIM1/Orai1 binding. In addition, we also showed that both the N and C termini of BmOrai1B are necessary for complete translocation of BmSTIM1 to the plasma membrane (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…We do not yet know whether the Orai-STIMct aggregates we observe are related to channel activation, or if they reflect the inactivation of channels that rapidly follows 2-APB-induced activation. Aggregation of Orai1 into m-sized clusters in the PM was recently reported to occur through altered electrostatic interactions of acidic residues in the Orai1 C terminus (33), possibly mediated by the STIMct. Whereas 2-APB causes a massive association between STIMct and Orai1, some constitutive association between STIMct and Orai1 can occur without 2-APB, a result agreeing with 3 recent reports in which STIM1ct was examined (24,30,34).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the model predicts that the helical stretch of basic residues (KIKKKR; Fig. 1 H, highlighted in purple) known to play a critical role in binding to Orai1 (Calloway et al, 2009(Calloway et al, , 2010Korzeniowski et al, 2010) is likely to be disrupted in STIM2β, whereas the regions responsible for STIM-STIM dimerization (Yang et al, 2012;Stathopulos et al, 2013) (Brandman et al, 2007). We applied thapsigargin (Tg) to deplete Ca 2+ stores and examine the effects of STIM2α and STIM2β on SOCE in HEK293 cells overexpressing Orai1 (Fig.…”
Section: Stim2β Is a Novel And Widely Expressed Stim2 Splice Isoformmentioning
confidence: 99%